O ENSINO DE ÁLGEBRA NO GINÁSIO ESPÍRITO-SANTENSE (1905 – 1941) - Virgens, Jessica Otaviano das (2021)
It seeks to analyze the teaching of Algebra in secondary education in Espírito Santo, in the period between 1905 and 1941. It seeks to answer the following guiding question: How was the teaching of Algebra characterized in secondary education in Espírito Santo between 1905 and 1941? Aiming to answer the research problem, its general objective is to identify the characteristics of the teaching of Algebra in secondary education in Espírito Santo, in the defined period. In addition, it presents, through official documents (laws, decrees and resolutions), the subdivisions of secondary education and their specificities; identifies Algebra within the scope of the teaching programs developed at Ginásio do Espírito Santo in the analyzed period; describes and analyzes the teaching of Algebra taught at GES from 1906 to 1940. The research was developed with a qualitative approach of historical documentary nature, discussed in the light of some assumptions of Cultural History, such as: representation, practice and appropriation proposed by Roger Chartier (2002); school culture, considered by Dominique Julia (2001) as a historical object; strategies and tactics described by Michel De Certeau (2009); and the history of school subjects, discussed by André Chervel (1990). Uses educational legislation as research sources; Teaching programs; Time books; School record books; School newspapers and exams. From the documentary analyzes, it was found that secondary education in the State had been subdivided into: vocational secondary education and secondary education itself. The first was in charge of the Escola Normal and the second, of the Ginásio EspíritoSantense. Algebra has always been present in the teaching programs of the junior high school, changing only its location in the curriculum. The contents that made up the discipline hardly changed in the first years. With the Francisco Campos Reformation in 1930, the fundamental course became five years long, and the last year was destined to the teaching of new algebraic contents: Limits, derivatives, series and integrals, in addition to Combinatorial Analysis and Newton's Binomial. With the analysis of the tests, we identified, in addition to the contents taught, the resolution procedures, the correction criteria and the way the student appropriated the material and the orientations given by the teacher. It also indicated a teaching focused on the techniques for solving algebraic operations, privileging mechanical and automatic calculation, without requiring the student to interpret the statement.